Hot Topics in Clinical Oral Implants Research: Recent Trends in Literature Coverage - Vesela Valkova; Ceeneena Ubaidha Maheen; Bernhard Pommer; Xiaohui Rausch-Fan; Rudolf Seeman (MDPI AG, 2016)
This systematic review looks at thematic trends in clinical research publications on dental implants. For this purpose, MEDLINE electronic searches as well as additional hand searches of six main journals in the field were conducted. A total of 2875 clinical studies published between 2001 and 2012 met the inclusion criteria and were subjected to statistical analysis. Hot topics in dental implant literature included immediate loading (14.3%), bone substitutes (11.6%), cross-arch full bridges (8.0%), and immediate implant placement (7.5%). A significant increase in scientific interest for immediate loading (+6.3%, p = 0.001), platform switching (+2.9%, p = 0.001), guided implant surgery (+1.9%, p = 0.011), growth factors (p = 0.014, +1.4%), piezoelectric surgery (+1.3%, p = 0.015), and restorative materials (+0.7%, p = 0.011) was found. A declining scientific interest in onlay grafting (−0.3%, p = 0.042) was recorded. The findings regarding current clinical oral implants research tie in with better-informed consumers and increased patient demands. Our results demonstrate an increasing interest in techniques that avoid complicated procedures such as bone grafting and that reduce treatment duration.